Spremembe v gibanju prebivalstva po naseljih SR Slovenije v obdobju 1961-1986 - Jakoš, Aleksander (Geografski vestnik, 1988)
In the Urban Planning Institute of SR Slovenia some basic data about Slovenian settlements were collected and put on the PC IBM XT Computer, namely: the number of population combined with the above sea level for the years 1961, 1971, 1981 and 1986. Analysis about population changes in the three periods showed some changes in the system of Slovenian settlements. In the period 1961-1971 rural exodus was still very strong as it had been all the time since the Second world war. On the other side a strong population concentration was taking place in main centers. In 3825 settlements (64% of total) the number of inhabitants was declining. The mayority of them were smaller settlements, with 40% of slovenian population. In the period 1971-1981 the share of settlements with depopulation was declining. In this period a gap among settlements with declining population appeared. In the majority of this settlements population decline was showing down, but in some of them it became even stronger. The number of settlements with fast growing population was raising and population concentration did not take place only in larger centers but even more in small ones. In the period 1981-1986 the number of settlements with population loss was still declining and their number for the first time was under half of the Slovenian settlements. On the other side the number of settlements with growing population was raising. For the first two periods (1961-1971, 1971-1981) it was typicall, that all three regions in West Slovenia were loosing population. The differences in population changes among other regions were moderate, but it was common for all of them that the number of settlements with depopulation was declining and the number of settlements with growing population was raising. In all the periods and especially in the last one (1981-1986) the Gorenjska region was favorated with nearly half of its settlements growing. For the present situation of population changes in settlements we can say that it is considerably improved, but we must recall that the number of population is still declining nearly in half of settlements and that the population decline is especially strong in 600 of them. Since in general this are the smallest and the most remote villages there is evident danger of reducing the cultivated and populated area of Slovenia.
Keywords: demografija; naselja; Naselja - analiza; poselitev; Slovenija